Efficiency of radiotherapy during local hyperthermia in the treatment of laryngeal and laryngopharyngeal cancer - E. L. Choinzonov (Opuholi Golovy i Šei, 2015)
Cancer of the larynx and laryngopharynx, which is accessible to visual and instrumental examination, remains the most relevant and complicated problem among head and neck malignances as before. Investigations show that the incidence of cancer at these sites in Russia in the last decade has risen from 4.5 to 9.67 %. This is a severe and poor prognostic form of cancer, which is characterized by its nonspecific early clinical manifestations, complex anatomic and topographic structure, and a high rate of regional metastases. The mainstay of treatment for head and neck cancer involves 3 components: surgery, chemotherapy, and radiotherapy (RT), which are performed alone or in combination. The most commonly used technique is combined, frequently crippling due to organ-removing operations. The clinical introduction of current radio modifiers, local and deep hyperthermia systems, is a promising approach to improving the results of treatment, to enhancing the radiation damage of RT, and to achieving the tumor regression sufficient for surgical intervention without augmenting the early and late toxicity inherent in chemoradiation treatment. The results of the performed study of 35 patients with T2–3N0–2M0 laryngeal and laryngopharyngeal cancer proved the high efficiency of local hyperthermia in treating malignancies in this region during both preoperative (grades III– IV therapeutic pathomorphism) and radical beam RT.